Mitos Dalam Keyakinan Msyarakat Jahiliyah di Tinjau dari Perspektif Al-Qur’an - Thoyib, Adil Muhammad; Hartoni, Hartoni; Patimah, Siti; Sajdah, Melisa; Saputra, M Indra (AL-MIKRAJ Jurnal Studi Islam dan Humaniora, 2025)
Myths are an inseparable part of the life of ignorant Arab society, even though they are not accepted by common sense and cannot be proven to be true, ignorant Arabs have a high adherence to myths. Violations of myths can have a broad impact on an individual's life, he can be ostracized from society because he is considered to have great disgrace, there is an opportunity for the perpetrator to experience shame that he cannot bear. The emergence of a fanatical attitude towards myths is a consequence of the strict inheritance of myths from generation to generation, resulting in a perception that increasingly establishes fanaticism towards myths. They believe that belief in myths can prevent them from life's accidents. The truth of this assumption cannot be tested because myths basically do not contain truth. This research aims to produce a complete perspective on myths based on the perspective of the Al-Qur'an and the Islamic attitude towards myths. If a critical analysis is carried out, there are at least three factors that cause the emergence of myths in the ignorant Arab society. First, weak realistic awareness. Second, limited knowledge caused by limited sensing, both direct and indirect. Third, the limitations of human reasoning at that time. There were various mythical practices that flourished during the Arab era of ignorance, two of which were the most prominent and became a marker of the identity of the Arab community of ignorance, namely the act of burying baby girls alive after birth from their mother's womb and the practice of idolatry. The Koran as a source of Islamic teachings rejects all forms of mythical practices that are contrary to Sharia law.